Socio Demographic Study of Gonorrhoea and Syphilis in Two Medical College Hospital and Two Private Chamber in Bangladesh (Medicine Today, 2013)
A total 300 (three hundred) Gonorrhea and Syphilis patients were studied in two Medical College Hospital (OPD) and two private Chamber to find out their Socio Demographic Characteristics. The patients were between 10 to 60 years of age and among them 250 were male and 50 were female. In this study found that the younger age group and unmarried persons are more prevalent. Regarding occupation, service holders are affected more and regarding their socioeconomic condition low and high income group population are also affected more. DOI: http://dx.doi.org/10.3329/medtoday.v25i1.15903 Medicine Today 2013 Vol.25(1): 18-20